Analysis of the Effectiveness of Hospital Administrative Systems in Improving the Quality of Healthcare Services (PT. LARPA JAYA PUBLISHER, 2023)
This study aims to analyze the effectiveness of hospital administrative systems in improving the quality of healthcare services. Effective administration plays a crucial role in accelerating service delivery, reducing administrative errors, and optimizing hospital resource management. This research employs a literature review method based on ten national and international scientific articles discussing the implementation of the Hospital Management Information System , administrative digitalization, and the relationship between administrative effectiveness and patient satisfaction. The findings indicate that integrated and technology-based administrative systems, such as Hospital Management Information System, significantly improve operational efficiency, data accuracy, and patient satisfaction. However, the success of implementation largely depends on human resource competence, training, and managerial support. Technical issues, user resistance, and limited infrastructure remain major challenges. Therefore, strengthening human resource capacity and conducting continuous evaluations of administrative systems are essential to ensure that hospitals can deliver optimal, efficient, and sustainable healthcare services. Keywords: hospital administrative system, SIMRS, efficiency, patient satisfaction, healthcare quality